Synchrony facilitates altruistic decision making for non-human avatars. (March 2022) - Fujiwara, Ken; Hoegen, Rens; Gratch, Jonathan; Dunbar, Norah E.
Abstract: Synchrony is a natural part of human interaction and is often associated with a variety of prosocial outcomes including affinity and rapport. The purpose of this research was to examine whether human negotiators would synchronize their movements when working with non-human avatars and if so, whether that would affect their perceptions of their negotiations. Results suggest that participants synchronized their movements with the movements of non-human negotiation partners, that greater synchrony was observed when participants engaged in an integrative negotiation compared to a distributive negotiation, and participants that engaged in synchrony reported greater affiliation with their non-human partner. Synchrony also lead to giving more to the non-human agent in an integrative negotiation whereas it had no significant impact on the outcomes in a distributive negotiation. Implications for human-machine interaction are discussed. Highlights: This study employed a factorial experimental design with the setting of negotiation (integrative, distributive) manipulated. Participants (N = 172) completed a negotiation experiment with a non-human avatar. Participants synchronized their movements with the movements of their non-human negotiation partners. Greater synchrony was observed when participants engaged in an integrative negotiation compared to distributive negotiation. Participants that engaged in synchrony reported greater affiliation with their non-human partner.